PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PERATAAN LABA TERHADAP RESPON INVESTOR DALAM SEKTOR KEUANGAN (Studi empiris pada perusahaan Sektor keuangan di BEI periode 2013-2015) - Tuti Juniarsih; Wida Purwidianti (Media Ekonomi, 2017)
The Research aimed to test effect of corporate social responsibility and profit equalization on investor’s response. independent variables in this study were corporate social responsibility and profit equalization. Dependent variable of this study was investor’s response (Cummulative abnormal return). This study used four control variables, those were: return on assets (ROA), debt to equity ratio (DER), firm size (FSIZE), and market share (MSHARE). This study was a quantitative research. The object of this study were financial firms listed on Indonesia Stock Exchange (BEI), There were 102 samples in this study obtained by using purposive sampling. Data analysis technique used in this research were descriptive statistics test, classical assumption test, multiple regression analysis, and hypothesis testing. The analysis showed that corporate social responsibility gave negative and significant effect partially on CAR. Profit equalization gave positive and insignificant partially on CAR.